2023
DOI: 10.3390/ijms241210028
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Desaturation Is Suppressed in Mir-26a/b Knockout Goat Mammary Epithelial Cells by Upregulating INSIG1

Abstract: MicroRNA-26 (miR-26a and miR-26b) plays a critical role in lipid metabolism, but its endogenous regulatory mechanism in fatty acid metabolism is not clear in goat mammary epithelial cells (GMECs). GMECs with the simultaneous knockout of miR-26a and miR-26b were obtained using the CRISPR/Cas9 system with four sgRNAs. In knockout GMECs, the contents of triglyceride, cholesterol, lipid droplets, and unsaturated fatty acid (UFA) were significantly reduced, and the expression of genes related to fatty acid metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…MiRNAs are a class of short-stranded, non-coding RNAs that exert their regulatory effects by inducing degradation and inhibiting translation of target genes through specific binding to 3 ′ -UTR. A growing body of studies has demonstrated their regulatory roles in various biological processes [14,15], including cell proliferation [31], differentiation [32], apoptosis [33], and so on. In addition, it has been observed that a single miRNA may target multiple genes, thereby exerting a multifaceted impact [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs are a class of short-stranded, non-coding RNAs that exert their regulatory effects by inducing degradation and inhibiting translation of target genes through specific binding to 3 ′ -UTR. A growing body of studies has demonstrated their regulatory roles in various biological processes [14,15], including cell proliferation [31], differentiation [32], apoptosis [33], and so on. In addition, it has been observed that a single miRNA may target multiple genes, thereby exerting a multifaceted impact [34].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) can regulate multiple target genes, while individual genes can also be regulated by diverse miRNAs [14,15]. The critical role of miRNAs in cellular processes, such as cell proliferation, apoptosis, lipid and protein synthesis, and body metabolism, is attributed to their regulation of various signaling pathway molecules [16].…”
Section: Introductionmentioning
confidence: 99%